Molecular Determinants of Substrate Selectivity of a Pneumococcal Rgg-Regulated Peptidase-Containing ABC Transporter - Charles Y. Wang (American Society for Microbiology, 2020)
ABSTRACT Peptidase-containing ABC transporters (PCATs) are a widely distributed family of transporters which secrete double-glycine (GG) peptides. In the opportunistic pathogen Streptococcus pneumoniae (pneumococcus), the PCATs ComAB and BlpAB have been shown to secrete quorum-sensing pheromones and bacteriocins related to the competence and pneumocin pathways. Here, we describe another pneumococcal PCAT, RtgAB, encoded by the rtg locus and found intact in 17% of strains. The Rgg/SHP-like quorum-sensing system RtgR/S, which uses a peptide pheromone with a distinctive Trp-X-Trp motif, regulates expression of the rtg locus and provides a competitive fitness advantage in a mouse model of nasopharyngeal colonization. RtgAB secretes a set of coregulated rtg GG peptides. ComAB and BlpAB, which share a substrate pool, do not secrete the rtg GG peptides. Similarly, RtgAB does not efficiently secrete ComAB/BlpAB substrates. We examined the molecular determinants of substrate selectivity between ComAB, BlpAB, and RtgAB and found that the GG peptide signal sequences contain all the information necessary to direct secretion through specific transporters. Secretion through ComAB and BlpAB depends largely on the identity of four conserved hydrophobic signal sequence residues previously implicated in substrate recognition by PCATs. In contrast, a motif situated at the N-terminal end of the signal sequence, found only in rtg GG peptides, directs secretion through RtgAB. These findings illustrate the complexity in predicting substrate-PCAT pairings by demonstrating specificity that is not dictated solely by signal sequence residues previously implicated in substrate recognition. IMPORTANCE The export of peptides from the cell is a fundamental process carried out by all bacteria. One method of bacterial peptide export relies on a family of transporters called peptidase-containing ABC transporters (PCATs). PCATs export so-called GG peptides which carry out diverse functions, including cell-to-cell communication and interbacterial competition. In this work, we describe a PCAT-encoding genetic locus, rtg, in the pathogen Streptococcus pneumoniae (pneumococcus). The rtg locus is linked to increased competitive fitness advantage in a mouse model of nasopharyngeal colonization. We also describe how the rtg PCAT preferentially secretes a set of coregulated GG peptides but not GG peptides secreted by other pneumococcal PCATs. These findings illuminate a relatively understudied part of PCAT biology: how these transporters discriminate between different subsets of GG peptides. Ultimately, expanding our knowledge of PCATs will advance our understanding of the many microbial processes dependent on these transporters.